Mandatory First Impressions: Happy Expressions Increase Trustworthiness Ratings of Subsequent Neutral Images. (February 2021) - Thierry, S. M.; Twele, A. C.; Mondloch, C. J.
First impressions of traits are formed rapidly and nonconsciously, suggesting an automatic process. We examined whether first impressions of trustworthiness are mandatory, another component of automaticity in face processing. In Experiment 1a, participants rated faces displaying subtle happy, subtle angry, and neutral expressions on trustworthiness. Happy faces were rated as more trustworthy than neutral faces; angry faces were rated as less trustworthy. In Experiment 1b, participants learned eight identities, half showing subtle happy and half showing subtle angry expressions. They then rated neutral images of these same identities (plus four novel neutral faces) on trustworthiness. Multilevel modeling analyses showed that identities previously shown with subtle expressions of happiness were rated as more trustworthy than novel identities. There was no effect of previously seen subtle angry expressions on ratings of trustworthiness. Mandatory first impressions based on subtle facial expressions were also reflected in two ratings designed to assess real-world outcomes. Participants indicated that they were more likely to vote for identities that had posed happy expressions and more likely to loan them money. These findings demonstrate that first impressions of trustworthiness based on previously seen subtle happy, but not angry, expressions are mandatory and are likely to have behavioral consequences.